Antibodies to an interfering epitope in hepatitis C virus E2 can mask vaccine‐induced neutralizing activity. Issue 6 (16th October 2015) - Kachko, Alla; Frey, Sharon E.; Sirota, Lev; Ray, Ranjit; Wells, Frances; Zubkova, Iryna; Zhang, Pei; Major, Marian E.
Abstract : Hepatitis C virus (HCV) neutralization occurring at the E2 region 412‐426 (EP‐I) could be enhanced when antibodies directed specifically to the E2 region 434‐446 (EP‐II) were removed from serum samples of persistently infected patients and vaccinated chimpanzees, a phenomenon of so‐called antibody interference. Here, we show that this type of interference can be observed in individuals after immunization with recombinant E1E2 proteins. One hundred twelve blinded serum samples from a phase I, placebo‐controlled, dose escalation trial using recombinant HCV E1E2 with MF59C.1 adjuvant in healthy HCV‐negative adults were tested in enzyme‐linked immunosorbent assay for binding reactivity to peptides representing the E2 regions 412‐426 (EP‐I) and 434‐446 (EP‐II). All samples were subsequently tested for neutralizing activity using cell‐culture HCV 1a(H77)/2a chimera, HCV pseudotype particles (HCVpp) H77, and HCVpp HCV‐1 after treatment to remove EP‐II‐specific antibodies or mock treatment with a control peptide. Among the 112 serum samples, we found 22 double positive (EP‐I and EP‐II), 6 EP‐II positive only, 14 EP‐I positive only, and 70 double negative. Depleting EP‐II antibodies from double‐positive serum samples increased 50% inhibitory dose (ID50 ) neutralizing antibody titers (up to 4.9‐fold) in up to 72% of samples ( P ≤ 0.0005), contrasting with ID50 neutralization titer increases in 2 of 70 double‐negative samples (2.9%; P > 0.5). In addition, EP‐I‐specific antibody levels in serum samples showed a significant correlation with ID50 neutralization titers when EP‐II antibodies were removed ( P < 0.0003). Conclusion: These data show that antibodies to the region 434‐446 are induced during immunization of individuals with recombinant E1E2 proteins, and that these antibodies can mask effective neutralizing activity from EP‐I‐specific antibodies. Elicitation of EP‐II‐specific antibodies with interfering capacity should be avoided in producing an effective cross‐neutralizing vaccine aimed at the HCV envelope proteins.(Hepatology 2015;62:1670–1682)